Dense distance map reconstruction of deformed surfaces using Moiré pattern analysis - Tu, Tong (2010)
Moiré patterns are the results of the interference fringes produced by superimposing two sets of repetitive gratings. These patterns are used in metrology for tasks such as strain measurements, vibration analysis and 3D surface reconstruction. Usually the setup used to generate Moiré patterns requires a grating on the surface to be analyzed and an additional semi-transparent reference grating. In this study, the regular spatial arrangement of sensor cells within a CCD camera is used to simplify this setup. Moiré fringes generated with the simplified setup are extracted with a simple, fast spatial domain algorithm. The relationship between the distances from points on a deformed surface to the imaging plane and the Moiré fringes frequency was derived and verified through a series of experiments. The Least- Squares Truncated Power Series Algorithm (L-STPSA) [1, 2] was adapted to extract the instantaneous frequency of the 1-dimensional Moiré waveform so that a dense distance map of the observed smoothly deformed surfaces can be reconstructed. Two applications were implemented to demonstrate how the proposed surface displacement measurement technique can be used to construct novel human-computer interfaces based on pressure sensitive touch surfaces.